Particle Size Measurement Using Acoustic Emission and Octave Band Analysis - Stetinova, Iveta; Pikula, Stanislav; Fialka, Jiří (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2025)
This paper investigates the application of Acoustic Emission (AE) for particle size measurement. AE is a nondestructive method that detects elastic waves generated by particle impacts. The study focuses on frequency-domain analysis using octave band analysis to examine how different particle sizes produce distinct AE signal responses.
Keywords: Granulometry; particle size distribution analysis; acoustic emission; octave band analysis